Osteoporosis, Rather Than Sarcopenia, Is the Predominant Musculoskeletal Disease in a Rural South African Community Where Human Immunodeficiency Virus Prevalence Is High: A Cross‐Sectional Study. (23rd November 2021) - Gregson, Celia L.; Madanhire, Tafadzwa; Rehman, Andrea; Ferrand, Rashida A.; Cappola, Anne R.; Tollman, Steven; Mokoena, Tshepiso; ,; Micklesfield, Lisa K.; Wade, Alisha N.; Fabian, June
ABSTRACT: The rollout of antiretroviral therapy globally has increased life expectancy across Southern Africa, where 20.6 million people now live with human immunodeficiency virus (HIV). We aimed to determine the prevalence of age‐related osteoporosis and sarcopenia, and investigate the association between HIV, bone mineral density (BMD), muscle strength and lean mass, and gait speed. A cross‐sectional community‐based study of individuals aged 20–80 years in rural South Africa collected demographic and clinical data, including HIV status, grip strength, gait speed, body composition, and BMD. Sarcopenia was defined by the European Working Group on Sarcopenia in Older People 2 (EWGSOP2) guidelines, and osteoporosis as BMD T ‐score ≤ −2.5 (if age ≥50 years). The mean ± standard deviation (SD) age of 805 black South African participants was 44.6 ± 14.8 years, 547 (68.2%) were female; 34 (13.2%) were men, and 129 (23.6%) women had HIV, with 88% overall taking anti‐retroviral therapy. A femoral neck T ‐score ≤ −2.5, seen in four of 95 (4.2%) men and 39 of 201 (19.4%) women age ≥50 years, was more common in women with than without HIV (13/35 [37.1%] versus 26/166 [15.7%]; p  = 0.003). Although no participant had confirmed sarcopenia, probable sarcopenia affected more men than women (30/258 [11.6%] versus 24/547 [4.4%]; p  = .001]. Although appendicular lean mass (ALM)/height 2 index was lower in both men and women with HIV, there were no differences in grip strength, gait speed, or probable sarcopenia by HIV status. Older age, female sex, lower ALM/height 2 index, slower gait speed, and HIV infection were all independently associated with lower femoral neck BMD. In conclusion, osteoporosis rather than sarcopenia is the common musculoskeletal disease of aging in rural South Africa; older women with HIV may experience greater bone losses than women without HIV. Findings raise concerns over future fracture risk in Southern Africa, where HIV clinics should consider routine bone health assessment, particularly in aging women. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).